(NbESEDY U DEREWA (B/s - d ((NmOSKWA (B:s (NqZYKI SLAW(B. (NKULXTURY(B,s, 2005)
(NrEZ(B.: (NANGL(B.s
(NbIBLIOGR(B.: (NS(B. 206-218.s
Keywords: (NsEMIOTIKAs; (NkULXTURAs; (NfILOSOFIQs; (NaNTROPOLOGIQ PO\TI^ESKAQs; (NtRADICII I OBY^AIs